Exploring ozone variability in the upper troposphere and lower stratosphere using dynamical coordinates - L. F. Millán; P. Hoor; M. I. Hegglin; M. I. Hegglin; M. I. Hegglin; G. L. Manney; G. L. Manney; H. Boenisch; P. Jeffery; D. Kunkel; I. Petropavlovskikh; H. Ye; et al. (Atmospheric Chemistry and Physics, 2024)
Ozone trends in the upper troposphere and lower stratosphere (UTLS) remain highly uncertain because of sharp spatial gradients and high variability caused by competing transport, chemical, and mixing processes near the upper-tropospheric jets and extratropical tropopause as well as inhomogeneous spatially and temporally limited observations of the region. Subtropical jets and the tropopause act as transport barriers, delineating boundaries between atmospheric regimes controlled by different processes; they can thus be used to separate data taken in those different regimes for numerous purposes, including trend assessment. As part of the Observed Composition Trends And Variability in the UTLS (OCTAV-UTLS) Stratosphere-troposphere Processes And their Role in Climate (SPARC) activity, we assess the effectiveness of several coordinate systems in segregating air into different atmospheric regimes. To achieve this, a comprehensive dynamical dataset is used to reference every measurement from various observing systems to the locations of jets and tropopauses in different coordinates (e.g., altitude, pressure, potential temperature, latitude, and equivalent latitude). We assess which coordinate combinations are most useful for dividing the measurements into bins such that the data in each bin are affected by the same processes, thus minimizing the variability induced when combining measurements from different dynamical regimes, each characterized by different physical processes. Such bins will be particularly suitable for combining measurements with different sampling characteristics and for assessing trends and attributing them to changing atmospheric dynamics. Overall, the use of equivalent latitude and potential temperature leads to the most substantial reduction in binned variability across the UTLS. This coordinate pairing uses potential vorticity (PV) on isentropic surfaces, thus aligning with the adiabatic transport of tracers.